A Dual‐Insertion Type Sodium‐Ion Full Cell Based on High‐Quality Ternary‐Metal Prussian Blue Analogs. Issue 11 (15th January 2018) - Peng, Jian; Wang, Jinsong; Yi, Haocong; Hu, WenJing; Yu, Yonghui; Yin, Jinwen; Shen, Yi; Liu, Yi; Luo, Jiahuan; Xu, Yue; Wei, Peng; Li, Yuyu; et al.
Abstract: Prussian blue analogs (PBAs) are especially investigated as superior cathodes for sodium‐ion batteries (SIBs) due to high theoretical capacity (≈170 mA h g −1 ) with 2‐Na storage and low cost. However, PBAs suffer poor cyclability due to irreversible phase transition in deep charge/discharge states. PBAs also suffer low crystallinity, with considerable [Fe(CN)6 ] vacancies, and coordinated water in crystal frameworks. Presently, a new chelating agent/surfactant coassisted crystallization method is developed to prepare high‐quality (HQ) ternary‐metal Ni x Co1− x [Fe(CN)6 ] PBAs. By introducing inactive metal Ni to suppress capacity fading caused by excessive lattice distortion, these PBAs have tunable limits on depth of charge/discharge. HQ‐Ni x Co1− x [Fe(CN)6 ] ( x = 0.3) demonstrates the best reversible Na‐storage behavior with a specific capacity of ≈145 mA h g −1 and a remarkably improved cycle performance, with ≈90% capacity retention over 600 cycles at 5 C. Furthermore, a dual‐insertion full cell on the cathode and NaTi2 (PO4 )3 anode delivers reversible capacity of ≈110 mA h g −1 at a current rate of 1.0 C without capacity fading over 300 cycles, showing promise as a high‐performance SIB for large‐scale energy‐storage systems. The ultrastable cyclability achieved in the lab and explained herein is far beyond that of any previously reported PBA‐based full cells. Abstract : A high rate and long‐life dual‐insertion sodium‐ion full cell is successfully fabricated without noticeable capacity fading over 300 cycles by using high‐quality ternary‐metal Prussian blue analogs with large structural strain‐suppression, which can extend a new avenue toward practical application of sodium‐ion batteries for large‐scale energy‐storage systems.